2022
DOI: 10.1177/15554120221088116
|View full text |Cite
|
Sign up to set email alerts
|

The COVID Season: U.S. Collegiate Esports Programs’ Material Challenges and Opportunities During the 2020–21 Pandemic

Abstract: During the COVID-19 pandemic, universities were among the first institutions to shift to an online model. As they did so, nascent collegiate esports program lost access to campus spaces and in-person connections, potentially destabilizing this rising industry. Conversely, universities also worked to provide students remote access to resources, and many components of esports already occur online. Therefore, collegiate esports may have adjusted to distancing measures, potentially strengthening their footholds on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This is especially true of the students themselves, who often function as the players and operators of esports endeavors (Harris et al, 2022;Taylor, 2020). In general, the involvement of multiple stakeholders with diverging interests in collegiate esports programs can lead to inconsistent oversight and organizational challenges (Cote et al, 2023).…”
Section: Resource Allocation and Program Developmentmentioning
confidence: 99%
“…This is especially true of the students themselves, who often function as the players and operators of esports endeavors (Harris et al, 2022;Taylor, 2020). In general, the involvement of multiple stakeholders with diverging interests in collegiate esports programs can lead to inconsistent oversight and organizational challenges (Cote et al, 2023).…”
Section: Resource Allocation and Program Developmentmentioning
confidence: 99%
“…Similarly, players are often tasked with moderating their program's Discord, allowing interpersonal relationships to influence how rules are applied in online spaces as well as in-person events. These issues may be worsened by COVID-19 as budget cuts may drive programs to cut funding for supervisory roles and rely on students instead (Cote et al, 2022).…”
Section: Reporting and Responsesmentioning
confidence: 99%
“…Also, challenges faced in esports happens when players are ill (such as during COVID-19 and flu season) that can be challenging for teams when players are not available to compete on campus with their team. However, Cote et al (2022) discussed that due to the COVID-19 pandemic, collegiate esports were able to thrive and become meaningful through digital technologies where players could compete from home utilizing campus resources when they could not be on campus due to illness. Similarly, Delello et al (2021) reported that positive outcomes students reported from playing esports included academic and personal benefits such as "social interaction, teamwork, and critical thinking skills" (p. 1) while the risks of esports were perceived as "esports gaming addiction; mental, social, emotional risks; lack of physical activity; and physical disorders associated with playing eSports" (p. 1).…”
Section: Reported Benefits and Risks Of Gamingmentioning
confidence: 99%